2021
DOI: 10.1038/s12276-021-00661-4
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary P62 deficiency leads to female infertility by impairing luteinizing hormone production

Abstract: P62 is a protein adaptor for various metabolic processes. Mice that lack p62 develop adult-onset obesity. However, investigations on p62 in reproductive dysfunction are rare. In the present study, we explored the effect of p62 on the reproductive system. P62 deficiency-induced reproductive dysfunction occurred at a young age (8 week old). Young systemic p62 knockout (p62-/-) and pituitary-specific p62 knockout (p62flox/flox αGSUcre) mice both presented a normal metabolic state, whereas they displayed infertili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…C57BL/6 mice were purchased from SLAC Laboratory Animal Co., Ltd. Atg7 flox/flox mice were gifts from Dr. Jianrong Wang, Medical College of Soochow University ( 20 ). SQSTM1 flox/flox mice were gifts from Dr. Hongting Zheng, Xinqiao Hospital, Army Medical University ( 21 ). All mice were housed with a standard 12-h light/dark cycle, climate-controlled, and pathogen-free facility.…”
Section: Methodsmentioning
confidence: 99%
“…C57BL/6 mice were purchased from SLAC Laboratory Animal Co., Ltd. Atg7 flox/flox mice were gifts from Dr. Jianrong Wang, Medical College of Soochow University ( 20 ). SQSTM1 flox/flox mice were gifts from Dr. Hongting Zheng, Xinqiao Hospital, Army Medical University ( 21 ). All mice were housed with a standard 12-h light/dark cycle, climate-controlled, and pathogen-free facility.…”
Section: Methodsmentioning
confidence: 99%
“…Other studies have demonstrated the importance of p62 by investigating the effects of p62 knockout. For example, loss of p62 in the pituitary has a detrimental effect on female mouse fertility due to impaired luteinizing hormone production through mitochondrial OXPHOS signaling ( Li X. et al, 2021 ). Another study showed that p62 protects against glycation-derived toxicity by driving the autophagic degradation of harmful age-associated advanced glycation end products ( Aragones et al, 2020 ).…”
Section: Contribution Of P62 Dynamics To Agingmentioning
confidence: 99%
“…Interestingly, p62 is deeply involved in cyclic follicle development through the hypothalamus–pituitary–ovary axis. The specificity of p62 in female reproduction is that it not only participates in regulating LH secretion in the pituitary [ 52 , 61 , 62 ], but also acts in response to FSH induction in ovarian GCs, as shown in this study. For instance, systematic knockout of p62 in mice resulted in obesity accompanied by female infertility, including pituitary dysfunction, as indicated by decreased LH levels during estrus, and ovarian dysfunction, as indicated by abnormal menstrual cycles, follicular formation, anovulation, and steroidogenesis [ 62 , 63 ].…”
Section: Discussionmentioning
confidence: 68%